THE RELEVANCE OF USING PROBLEM SOLVING METHOD IN TEACHING THE SCIENCE OF INHERITANCE IN ISLAMIC EDUCATION TO UPPER LEVEL STUDENTS - Halabi, Kabara Auwal; Aiyetoro, Abdulkareem Idris (FIKRAH, 2024)
The science of inheritance is one of the branches of jurisprudence of Islamic education, which means the distribution of inheritance to the heirs after death. Many methods for teaching inheritance topics of Islamic education were suggested and vividly elaborated by different scholars. Like any other subjects, and for the importance and difficulty of the subject (science of inheritance) amongst Islamic education subjects, there is still needed to bring more specific method to help achieve its topics effectively. This is what present study focused to elaborate. The qualitative method of philosophical analysis is employed for the purpose of this study. From the findings, relevance of using problem solving method in teaching inheritance topics of Islamic education was intensely highlighted. Therefore, Islamic education teachers are recommended to make the method completely utilised in teaching the subject, and a good strategy should be carefully chosen to help achieve a good provision of the method.